A Sheathless Retrograde Approach Via the Popliteal Artery Is Useful and Safe for Treating Chronic Total Occlusions in the Superficial Femoral Artery. (April 2014) - Tokuda, Takahiro; Hirano, Keisuke; Muramatsu, Toshiya; Tsukahara, Reiko; Nakano, Masatsugu
Purpose: To compare the safety and success of a retrograde approach using a microcatheter vs. a sheath in the treatment of superficial femoral artery (SFA) chronic total occlusions (CTOs). Methods: From April 2007 to December 2012, 188 consecutive patients underwent EVT for 229 de novo SFA CTOs using the retrograde approach in 68 patients (35 men; mean age 72 years). This cohort was divided into cases performed with a 4-F or 6-F sheath (n=28, 36 limbs) and those with a 2.1-F microcatheter (n=35, 49 limbs). The primary outcomes were mean time to hemostasis and number of intra- and postoperative puncture site complications, as well as the success of popliteal artery puncture, lesion crossing, and reperfusion. Results: There were no significant differences between two groups in baseline characteristics. PA puncture was successful in all limbs, and the success in crossing the lesion with the wire was not significantly different (91.9% in the sheath group vs. 89.8% in the microcatheter group). Mean time to hemostasis was 8.9±8.8 minutes in the microcatheter group vs. 47.7±13 minutes in the sheath group (p<0.0001). There was a significant difference in intraoperative and postoperative complications (22.2% in the sheath group vs. 2.0% in the microcatheter group, p=0.002). Conclusion: Based on this retrospective analysis, the use of a microcatheter for SFA CTO retrograde access appears to be superior to 4-F or 6-F sheaths in terms of shorter time to hemostasis and fewer complications.